(untitled) (Annals of Medical Research, 2021)
Aim: Respiratory distress syndrome (RDS) is a lung failure that starts after birth. Because of deficiency of surfactants in alveoli, this becomes one of the most important causes of morbidity and mortality in preterm neonates. In this study, we tried to compare the outcomes of two types of natural surfactant, derived from same animal and aimed to manage the anxiety of clinicians while they are choosing the most appropriate preparate for RDS treatment.Material and Methods: Newborns hospitalized in Baskent University Ankara Hospital Neonatal Intensive Care Unit between January 2017 and August 2018 and administrated with calfactant and beractant for RDS treatment were retrospectively examined.Results: A total of 57 neonates were enrolled into the study. It was indicated that 38 (66.7%) of neonates were administered beractant and 19 (33.3%) were administered calfactant. We did not find any significant difference between beractant and calfactant groups, according to their genders, gestational weeks, their intubation situations, the duration of the oxygen requirement, antibiotic usages and the durations of mechanical ventilation. It was determined that calfactant-administered neonates needed statistically more repeat dose, than those in the beractant group (p= 0.029). Conclusions: We examined two natural surfactant preparates derived from same animal. Calfactant which has some conflicting reports was newly introduced to our unit for RDS treatment. This study aimed to identify the most appropriate treatment modality for RDS. It would be more instructive to plan larger and more creative studies to examine possible differences among natural surfactant preparates.